PB18 Minor injury units: are they a safe alternative for emergency treatment of orthopaedic minor injuries?. (19th March 2012) - Smith, J; Balogun-Ojuri, B; Chesser, T
Abstract : Objectives and Background: With the drive to bring the provision of emergency care into the community, the number of minor injury units (MIU) is rising. While these units may lead to improved access to medical services, they must be introduced without compromise to quality of patient care. This study aims to determine whether the quality of care delivered by two MIU in the community is akin to that provided by a hospital Emergency Department (ED), and thus a safe and efficient use of NHS time and resources. Method: Retrospective case note review of orthopaedic outpatient fracture clinic referrals from two MIU (one fully established and one recently opened) and one teaching hospital ED. Units were assessed on their accuracy of diagnosis and initial management. Results: A total of 439 orthopaedic outpatient referrals were included from July–September 2010. Appropriate management was achieved in 63% of referrals from the newly opened MIU, compared with 81% from the teaching hospital ED (p=0.003). 64% of the newly opened MIU patients were correctly diagnosed, versus 83% at the ED (p=0.001). A quarter of patients who attended the recently opened MIU received inappropriate initial treatment (p=0.04). There was no significant difference between results for the established MIU and the ED in any measure. Conclusion: For the management of minor orthopaedic injury, well supported nurse-led centres can provide a safe and effective alternative to doctor led care, thus reducing the workload on already burdened hospital EDs. However, new nurse-led MIU must have close observation and tight regulation to prevent the inefficient use of NHS resources and more importantly a risk to patient safety and quality of care.